A prova da existência dos corpos: a análise de Malebranche a partir da “visão em Deus” - Henning, Vanessa (2018)
This paper aims to examine certain difficulties related to cartesian explanation about knowledge of existence of bodies from Malebranche’s thinking. They are articulated from two groups of arguments. The first one is about the theme and tensions in cartesian thesis of dualism, and the second one represents Malebranche’s thesis about unintelligibility, by the human being, the world and, therefore, about the fact of being inappropriate to human spirit to desire to capture and speak the truth to the world. Regarding the theme of dualism, its consequences reflect the impossibility of the spirit and the body relate their own immediately. Concerning the second argument, Malebranche’s analysis ends up dismissing the power of rational human faculty in what refers to unintelligibility of all things, in so far it shows the limits of perception and the inability of man to demonstrate an existing world beyond what is manifested to his mind. Our hypothesis is that Malebranche intends to establish a casual solution to cartesian thesis of existence of bodies and knowledge of the world. This way, human intellect is totally recipient of light and divine action – it is in God that you can find the world of intelligibility: in consequence, our knowledge and our sensible perception of bodies happen because of divine action upon us, and because of that Malebranche claims our bodies only can be recognized by the ideas in God. In the first chapter, it is presented Malebranche’s position related to the way how the knowledge is given, which central thesis consists in showing how it occurs, not by the relation between our mind and world anymore, but by the relation of our spirit with God. In the second chapter, we can see Malebranche’s radicalization in his causality analysis, ending in thesis that a man is unable of demonstrating any causal relation between his thinking and corporeal reality. Thereby, the existence of bodies can not be demonstrated by human reason. In the third chapter, it is explained the reasons why faith is instituted as the way to be sure of the existence of the bodies. Malebranche understands the certain of this existence as a human recognition to divine grace, whereas God is the true and necessary cause of all our perceptions. Our conclusion is that Malebranche takes to the last consequences certain thesis of cartesian thinking, intending to point the human impotence about the unveiling of the real: we do not know our own bodies by the ideas we have about them, countersigned by God, good and truthful, but by ideas in God, of which we take part.